2020
DOI: 10.1021/acsami.0c18273
|View full text |Cite
|
Sign up to set email alerts
|

Self-Distinguishing and Stimulus-Responsive Carrier-Free Theranostic Nanoagents for Imaging-Guided Chemo-Photothermal Therapy in Small-Cell Lung Cancer

Abstract: Lack of tumor targeting and low drug payload severely impedes various nanoagents further employed in small-cell lung cancer (SCLC). Therefore, how to develop a new targeting ligand and enhance drug payload has been an urgent need for SCLC therapy. Herein, we first sift and verify that capreomycin (Cm) has a high affinity toward CD56 receptors overexpressed on SCLC cells. Motivated by the concept of self-targeted drug delivery, Cm is selected as the specific targeting ligand toward CD56 receptors and chemodrug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…275–277 Therefore, developing GSH probes is of interest in understanding its role in cancer development and to facilitate the application of GSH-targeted cancer therapy. Due to the deep tissue penetration of PA imaging, many activatable PA probes have been developed as tools to study the in vivo behavior of GSH, 278–289 and here we introduce some recent progress in this area.…”
Section: Activatable Pa Probesmentioning
confidence: 99%
“…275–277 Therefore, developing GSH probes is of interest in understanding its role in cancer development and to facilitate the application of GSH-targeted cancer therapy. Due to the deep tissue penetration of PA imaging, many activatable PA probes have been developed as tools to study the in vivo behavior of GSH, 278–289 and here we introduce some recent progress in this area.…”
Section: Activatable Pa Probesmentioning
confidence: 99%
“…Light-triggered drug release can also be combined with other stimuli, including internal stimuli (e.g., pH [ 38 , 39 , 40 ], enzyme [ 41 ], glutathione [ 42 , 43 ], and other external stimuli (e.g., radio frequency [ 44 ]), for enhanced targeted therapy to lung cancer. For example, as the tumor microenvironment is enriched in esterase, introducing the esterase-labile ester bond to the therapeutic system can achieve tumor microenvironment-responsive drug release in situ.…”
Section: Light-responsive Nanocarriersmentioning
confidence: 99%
“…Furthermore, molecules that absorb light and generate heat or ROS sometimes can also emit fluorescence or transfer the heat to photoacoustic (PA) signal and thus are employed for imaging diagnosis during the therapeutic process. For instance, indocyanine green (ICG) is a typical photothermal molecule and can also be utilized for NIR fluorescence and PA imaging [ 43 ]. Other fluorescent molecules, such as IR780 [ 46 , 47 ], Cy7 [ 48 ], and NIR770 [ 41 ], are also applied as theranostic agents to the treatment of lung cancer.…”
Section: Light-responsive Nanocarriersmentioning
confidence: 99%
“…In Liu et al's study, PEG modified graphene oxide quantum dots were developed to load DOX and ICG, which displayed much stronger tumor growth inhibition than monotherapy [24]. Moreover, ICG could be applied in the detection of tumor by PA imaging under NIR laser with the aid of nanocarriers to improve its stability in vivo [25,26]. For instance, Shen et al built ICG-loaded and folic acid-modified multiwalled carbon nanotubes, and demonstrated that the nanoplatforms exhibited excellent photostability for tumor targeted PA imaging and phototherapy [27].…”
Section: Of 11mentioning
confidence: 99%